A Queering of Black Theology - Kornegay, E. author. aut Link
IX, 199 p.
Keywords: Kornegay's brilliant and insightful use of James Baldwin's literary genius offers a way forward that promises to overcome the divide between religion and sexuality that is of crucial importance not only for black church and theology but for socio-political-religious and theological discourse generally.